2013
DOI: 10.5539/jfr.v2n2p136
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Stevia rebaudiana on the Growth and Survival of Lactobacillus rhamnosus GR-1 and Sensory Properties of Probiotic Yogurt

Abstract: This study evaluated the effect of various sweetening agents on sensory properties of probiotic yogurt. The growth and survival of Lactobacillus rhamnosus GR-1 in yogurt was measured at 1, 14 and 28 days of storage. Bacterial growth reached a range of 10 8 -109 Colony Forming Units (CFU) ml -1 over the storage period for six probiotic yogurt samples (0.12% stevia, 0.12% stevia-inulin-chromium (SIC), 1.0% sucralose, 5.0% sucrose, 6.0% xylitol and a control). Sensory panelists (n = 109) used a 9-point hedonic sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…It was reported that stevia did not affect the survival of Lact. rhamnosus GR‐1 in yogurt and was suggested for incorporation into probiotic yogurt (Weber and Hekmat ). However, a slight inhibitory effect on some human gut microbiota groups incubated with stevioside or rebaudioside A was observed when the influence of stevia glycosides on the human intestinal microbiota, among them lactobacilli, was recently analysed (Gardana et al .…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that stevia did not affect the survival of Lact. rhamnosus GR‐1 in yogurt and was suggested for incorporation into probiotic yogurt (Weber and Hekmat ). However, a slight inhibitory effect on some human gut microbiota groups incubated with stevioside or rebaudioside A was observed when the influence of stevia glycosides on the human intestinal microbiota, among them lactobacilli, was recently analysed (Gardana et al .…”
Section: Introductionmentioning
confidence: 99%
“…Also, it appears that sweetening potency and the lingering of sweet aftertaste of Stevioside are affected by factors such as concentration of stevia, synergistic or inhibitory effects (by what? ), temperature of medium, and viscosity of food and characteristics of the dispersion media [29]. Therefore, further research is needed to examine sensory profile of Stevia sweetened beverages in reference to above mentioned parameters.…”
Section: Discussionmentioning
confidence: 99%
“…The chocolate milk with 18g of sucrose with stevia was more accepted and sample with NSA and with stevia (C) had lower notes [22][23][24][25]. Panelists significantly prefer chocolate milk with 18g sucrose and stevia.…”
Section: Milksmentioning
confidence: 99%